AL-ṢAHĪFAH AL-MADANIYAH: Konstitusi Negara Masa Kepemimpinan Nabi Muhammad Saw - Abu Bakar (Fakultas Syariah (Syari'ah Faculty ), 2016)
In Islamic History, the period of prophet Muhammad (PBUH) was the most ideal period of leadership even viewed from the thought of modern politics. It was a glorious period especially for Arabs in the seventh century. The presence of the prophet has changed Arabian jahiliah character into laudable morality based on Islamic teachings. In Madina, the prophet was well-welcomed as a leader. This was very different from the condition in Mecca in which many people hated him so much. In madina, he succeeded in establishingsocio-politics between Muslim and non-Muslim or between Arab and non-Arab. The basic element of the socio-politics was al-Ṣahīfah al-Madaniyah in which all persons of Madiana society were bounded according to common agreement. Ṣahīfah consisted of valuable principles: integration, brotherhood, equality, freedom, justice, legal security, defence, peace, and leadership. Based on constitutional theory, al-Ṣahīfah al-Madaniyah was a form of constitutional state. In other words, during the prophet’s period, Madina was a state with an ideal type of social system.